Financial Literacy, Financial Attitude, and Internal Locus of Control towards Personal Financial Management - Yunarsi Yunarsi (STKIP Singkawang, 2022)
The purpose of this study was to determine the effect given by financial literacy, financial attitude, and internal locus of control on personal financial management. This study used a mixed method. The population in this study were small business actors in Anggilowu Village, Mandonga District, Kendari City which consisted of 131 people as research samples. The research sample was selected using a probability sampling technique, namely cluster sampling. Data collection techniques used primary data by disseminating questionnaires, then the data were analyzed using multiple regression analysis using the SPSS version 22 program. The results showed that financial literacy, financial attitude, and internal locus of control had a positive and significant influence on personal financial management. It means that the better the level of financial literacy, financial attitude, and internal locus of control of a person, it will provide a proportional relationship in line with the increase in a person's financial management.